On the molecular properties of graphene-pyrazines conjugated Ru and Fe complexes: Computational insights - Abdulilah Dawoud, Bani-Yaseen (2020)
Graphene and related materials can exhibit substantial molecular properties of significant importance in various landscapes of interests including catalysis. On the other hand, transition-metal-based molecular heterogeneous electrocatalysts can demonstrate enhanced catalytic usability compared to homogeneous analogues concerning recoverability and durability. We present in this study computational investigations on selected molecular properties graphene-based heterogenized molecular complexes of the (2,2′-bipyridyl)-metal complexes, [M(bpy)3]2+ (M = Fe, Ru). The computational study was conducted using the density functional theory (DFT) approach with an implicit solvation model (IEFPCM). Interestingly, the DFT results revealed that the key structural properties of the complexes are not disrupted by heterogenization. Also, the DFT-based calculated reduction potential of all examined species revealed a good agreement between the graphene-based heterogeneous electrocatalysts and their corresponding homogeneous analogues in terms of the redox potentials and the corresponding molecular properties in implicit acetonitrile. The finding reported herein demonstrates the applicability of graphene in covalent heterogenization of a molecular catalyst. As such, these computational insights can be useful in future efforts toward developing efficient heterogeneous molecular catalysts for a wide range of important chemical transformations.